2021
DOI: 10.4102/jtscm.v15i0.583
|View full text |Cite
|
Sign up to set email alerts
|

The impact of measuring driver performance on the bulk fuel supply chain

Abstract: Background: The distribution of bulk fuel products to customers is one of the key activities in the downstream petroleum supply chain. For this activity to be effected successfully, three groups of supply chain participants, drivers, supervisors and customers, play key roles. Truck drivers are responsible for conveying the final product to the customer, whilst supervisors ensure that trucks are dispatched on time, driver performance is monitored and performance feedback is properly communicated to drivers. Cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…This has helped to enhance the performance of the businesses. In South Africa, Sithole (2017) observed that the SMEs in South Africa are increasingly utilizing e-procurement technologies to enhance their operations. One of the most commonly used technological strategies adopted include einvoicing.…”
Section: Introductionmentioning
confidence: 99%
“…This has helped to enhance the performance of the businesses. In South Africa, Sithole (2017) observed that the SMEs in South Africa are increasingly utilizing e-procurement technologies to enhance their operations. One of the most commonly used technological strategies adopted include einvoicing.…”
Section: Introductionmentioning
confidence: 99%